2014
DOI: 10.1038/ki.2013.544
|View full text |Cite
|
Sign up to set email alerts
|

A multicenter cross-sectional study of circulating soluble urokinase receptor in Japanese patients with glomerular disease

Abstract: Elevated serum-soluble urokinase receptor (suPAR) levels have been described in patients with focal segmental glomerulosclerosis (FSGS) in several different cohorts. However, it remains unclear whether this is the case for Japanese patients and whether circulating suPAR can be clinically useful as a diagnostic marker. To determine this, we measured serum suPAR levels in 69 Japanese patients with biopsy-proven glomerular diseases in a cross-sectional manner. The serum suPAR levels showed a significant inverse c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
62
2

Year Published

2014
2014
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 76 publications
(69 citation statements)
references
References 25 publications
(38 reference statements)
5
62
2
Order By: Relevance
“…However, our results showed suPAR in type 2 DM without DN did not significantly increase as compared with healthy subjects. Some [21] and also found suPAR is inversely related to eGFR, which was consistent with our findings. The molecular weight of suPAR ranges from 20 to 50 kDa, which would pass through glomerular filtration.…”
Section: Discussionsupporting
confidence: 95%
“…However, our results showed suPAR in type 2 DM without DN did not significantly increase as compared with healthy subjects. Some [21] and also found suPAR is inversely related to eGFR, which was consistent with our findings. The molecular weight of suPAR ranges from 20 to 50 kDa, which would pass through glomerular filtration.…”
Section: Discussionsupporting
confidence: 95%
“…These findings have been confirmed in two pediatric multicenter study cohorts-the FSGS clinical trial (FSGS-CTR) and the PodoNet consortium-and in a Chinese adult cohort with FSGS [2,3], but not in a single-center pediatric study [4]. Two recent crosssectional studies in adult patients and a further large pediatric study found that suPAR levels could not discriminate FSGS from other glomerular diseases [5][6][7]. However, serum suPAR levels were inversely correlated with renal function [estimated glomerular filtration rate(eGFR)] in all three studies.…”
Section: Introductionmentioning
confidence: 51%
“…In addition, circulating suPAR has been reported to positively associate with carotid atherosclerosis and increased cardiovascular risk in CKD (29,30), and is also reported to be involved in renal damage that might progress to CKD (31). suPAR was previously postulated to represent a specific biomarker for primary FSGS, but recently has been identified in other glomerular diseases and negatively correlated with GFR (23,30,32). In this study, the systemic level of suPAR in RVH was higher than observed in primary FSGS (approximately 4.6 ng/ml) (22,33).…”
Section: Discussionmentioning
confidence: 99%
“…The soluble urokinase plasminogen activator receptor (suPAR) circulates in the plasma, and its level correlates with atherosclerosis, cardiovascular risk, and subclinical organ damage (21). Furthermore, suPAR levels increase in CKD associated with some glomerular diseases (22,23). The degree to which levels of these ubiquitous biomarkers are altered in patients with essential hypertension (EH) or renovascular hypertension (RVH) remains unknown.…”
Section: Introductionmentioning
confidence: 99%